2010
DOI: 10.1144/sp347.9
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentological control of fluid flow in deep marine turbidite reservoirs: Pierce Field, UK Central North Sea

Abstract: The Pierce Field in the Central UK North Sea is a twin diapir structure that produces from the Paleocene Forties Sandstone Member (Forties Sandstone). Different hydrocarbon–water contacts encountered in the wells around both diapirs have been variously ascribed to a hydrodynamically tilted oil–water contact or else some form of stepped (compartmentalized) contact. Recent reinterpretation of the structure, sedimentology and fluid geochemistry has indicated that the stratigraphic architecture of the reservoir is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…12). The diapirs protrude through the Sele Formation in this location, and seismic data highlight 'channelized fairways' wrapping around these (Scott et al 2010). Wells logs and core indicate that the channel fairways are characterized by thick, amalgamated sandstone facies (Fig.…”
Section: Syndepositional Diapir-modified Settingsmentioning
confidence: 79%
See 2 more Smart Citations
“…12). The diapirs protrude through the Sele Formation in this location, and seismic data highlight 'channelized fairways' wrapping around these (Scott et al 2010). Wells logs and core indicate that the channel fairways are characterized by thick, amalgamated sandstone facies (Fig.…”
Section: Syndepositional Diapir-modified Settingsmentioning
confidence: 79%
“…Towards Pierce, T70 channels were funnelled through remnant Lista (T60) palaeotopography and active salt diapirs, resulting in the rechannelization of parts of the T70 lobe system (cf. Scott et al 2010). Later cannibalization of the lobe complex is noticeable towards Quadrant 30, with additional feeder channels identified.…”
Section: T70 Sequence (Sele S1/dornoch Formation)mentioning
confidence: 96%
See 1 more Smart Citation
“…Some Paleogene oilfields in UK water have a complex architecture, formed by turbidite channels, sheet turbidite sandstones and sealing faults . Examples include the Schiehallion Field and Pierce Field (Gainski et al, 2010;Scott et al, 2010). In the Southern North Sea, it has been reported that the Triassic Bunter Sandstone aquifer is more suitable for CO2 storage reservoir than the Permian Rotliegend Sandstone because it has less compartmentalization problems (Holloway et al, 2006).…”
Section: The Geological Risks Of a Proven Reservoirmentioning
confidence: 99%
“…Ongoing movement subsequently deformed these deposits, inducing steep dips, overturned stratigraphy, injection and faulting (e.g. Stewart 2007;Scott et al 2010). In these situations, it is critical to understand the impact on reservoir sand deposition of the deforming seafloor and the subsequent structural deformation (Charles & Ryzhikov 2015).…”
Section: Regional Settingmentioning
confidence: 99%